NR SOSIALISASI METODE ALTERNATIF MENGUADRATKAN BILANGAN BULAT YANG MUDAH DAN MENYENANGKAN: - - Nurul Astuty Yensy; Rita Shintia (Universitas Bengkulu, 2025)
Mathematics needs to be taught to students to equip them with logical, analytical, systematic, critical, and creative thinking skills. Elementary school teachers rarely implement fun learning strategies in mathematics. For example, in the topic of squaring integers for large numbers. Generally, students are told to memorize the squaring of numbers 1 to 10, but for hundreds or even thousands, it starts to make students bored and difficult to calculate. This is compounded by the learning strategies given by teachers using conventional methods or stacking methods. This condition is also experienced by students of Elementary School 88 Bengkulu Tengah. An initial survey conducted by interviewing several teachers there found information that the majority of students are weak in mathematics, and they are also less motivated to learn. Therefore, it is deemed necessary to conduct Socialization of Alternative Methods for Squaring Integers that are Easy and Fun for Teachers of Elementary School 88 Bengkulu Tengah. The results of the activity showed that the knowledge of Elementary School 88 Bengkulu Tengah teachers about alternative methods in squaring integers increased after being given socialization and seminars during training activities. This is reinforced by the results of the teacher motivation questionnaire for participating in this training, which is classified as good, as many as 100% of the participants gave a positive response to this activity. The ability and skills of teachers at SD N 88 Bengkulu Tengah in applying the integer squaring method as an easy and fun alternative method for solving problems are very good, namely 100% of teachers have been able to apply it to various solutions to number squaring problems. Keywords: Alternative Method, Squaring Integers.